2021
DOI: 10.3390/md19020054
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota, a New Playground for the Omega-3 Polyunsaturated Fatty Acids in Cardiovascular Diseases

Abstract: Several cardioprotective mechanisms attributed to Omega-3 polyunsaturated fatty acids (PUFAs) have been studied and widely documented. However, in recent years, studies have supported the concept that the intestinal microbiota can play a much larger role than we had anticipated. Microbiota could contribute to several pathologies, including cardiovascular diseases. Indeed, an imbalance in the microbiota has often been reported in patients with cardiovascular disease and produces low-level inflammation. This inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 118 publications
(135 reference statements)
0
13
0
Order By: Relevance
“…The coupled complex of TAB-1and TAK-1 is a merging point for stimuli induced by the toll-like receptor 4 (TLR4) signaling pathway, including tumor necrosis factor receptor (TNFr) [17,18]. Similarly, a possible cardioprotective mechanism may be attributed to the activation of protein kinases B such as AKT, previously recognized as interplaying with biochemical pathways known as reperfusion injury salvage kinase (RISK) [19]. When the onset of reperfusion is initiated, these kinases bestow cardio-protective effects via mitochondrial permeability transition pore (mPTP) opening suppression.…”
Section: Second ω-3 Pufa Interact Directly With Proteins and Membrane Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The coupled complex of TAB-1and TAK-1 is a merging point for stimuli induced by the toll-like receptor 4 (TLR4) signaling pathway, including tumor necrosis factor receptor (TNFr) [17,18]. Similarly, a possible cardioprotective mechanism may be attributed to the activation of protein kinases B such as AKT, previously recognized as interplaying with biochemical pathways known as reperfusion injury salvage kinase (RISK) [19]. When the onset of reperfusion is initiated, these kinases bestow cardio-protective effects via mitochondrial permeability transition pore (mPTP) opening suppression.…”
Section: Second ω-3 Pufa Interact Directly With Proteins and Membrane Channelsmentioning
confidence: 99%
“…Another possible mechanism for how dietary ω-3 PUFA might mitigate the adverse effects of cardiovascular diseases arose with their potentiality to decrease the abundance of gut bacteria producing trimethylamine (TMA), a precursor of trimethylamine-N-oxide (TMAO), and which was previously reported in atherosclerotic plaque formation [14,19].…”
Section: Mitigation Of Adverse Effects Related To Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence indicates that ω3PUFAs can influence enteric microorganisms to protect the cardiovascular system by inhibiting the TMA produced by bacteria, promoting anti-inflammatory-active bacteria to create butyrate and downregulating proinflammatory fingers. In addition, ω3PUFAs defend gut barrier integrity to hold back intestinal contents from circulation ( 93 ). However, it was also reported that ω6PUFAs at high concentrations might reduce the influence of ω3PUFAs on the cardiovascular system ( 94 ).…”
Section: Lipidsmentioning
confidence: 99%